2023
DOI: 10.1002/lpor.202200277
|View full text |Cite
|
Sign up to set email alerts
|

Optical Vortex Brillouin Laser

Abstract: Optical vortices, which have been extensively studied over the last decades, offer an additional degree of freedom useful in many applications, such as optical tweezers and quantum control. Stimulated Brillouin scattering (SBS), providing a narrow linewidth and a strong nonlinear response, has been used to realize quasi‐continuous wave lasers. Here, stable oscillation of optical vortices and acoustic modes in a Brillouin laser based on chiral photonic crystal fiber (PCF) is reported, which robustly supports he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In addition, twisted fibers have recently made good progress in fields such as amplification and lasers [9,14]. Therefore, when characterizing these devices, researchers will design corresponding experimental plans according to their needs.…”
Section: Characterization Process Of Chiral Twisted Fibersmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, twisted fibers have recently made good progress in fields such as amplification and lasers [9,14]. Therefore, when characterizing these devices, researchers will design corresponding experimental plans according to their needs.…”
Section: Characterization Process Of Chiral Twisted Fibersmentioning
confidence: 99%
“…Compared to traditional SMFs, twisted structures in the form of MOFs offer more choices and greater possibilities in the field of twisted fiber applications due to their versatile and flexible structure. In addition to enhanced mode selection, mode field control, and OAM mode generation [48][49][50], chiral twisted microstructured fiber (CTMOF) has also been found to have great potential in fields such as lasers [9], sensing [51][52][53], and transmission [54][55][56]. Here, we have summarized some applications, including chiral twisted photonic crystal fiber (CTPCF), chiral twisted hollow-core fiber (CTHCF), and chiral twisted multicore fiber (CTMCF), and found that microstructured fibers play a crucial role in improving the functionality of twisting.…”
Section: Chiral Twisted Microstructured Optical Fibersmentioning
confidence: 99%
See 2 more Smart Citations